Active directory : administrator's pocket consultant - Stanek, William R. (Microsoft Press, 2009)
Provides information on the administration of Active Directory in Windows Server 2008, covering such topics as adding and removing writable domain controllers, configuring catalog servers, evaluating sites, and employing command-line utilities.